The Role of Social Protection in Reducing Poverty in Ghana - Honorati, Maddalena (World Bank, Washington, DC, 2015)
The National Social Protection Policy under preparation establishes objectives, scope, and institutional and administrative arrangements that are designed to enhance the complementarities and coordination of the SP system, the objective being to halve extreme poverty by 2025.